Democracy and curriculum—the task still before us. (July 2020) - Wahlström, Ninni
This article explores how John Dewey's concept of democracy can contribute to our understanding of what is required from education amid growing nationalism and populism, even in what are usually perceived as established democracies. The purpose of the study is to explore how standards-based curricula for citizenship education can be problematised in relation to the broad concept of democracy. The meaning of citizenship education in curricula is examined through two cases from western countries (Sweden and the USA) with standards-based curricula. These social studies curricula deal with democracy as something 'to teach about', rather than focusing on helping students learn to understand and recreate democracy for their own generation. However, the concept of democracy, as a moral and ethical ideal, becomes difficult to express in a curriculum logic of standards and knowledge outcomes emphasising measurability. Now, when democracy is challenged, also seems to be the right time to confront the logic of a standards-based curriculum and the selective traditions of subjects within the social studies, as well as to ask the questions 'why?' and 'what for?' in relation to basic social values and students' competences.